No caminho das artes marciais: a relação mestre e discípulo como educação sensível - Silva, Luiz Arthur Nunes da (2014)
This research reflects the relationship between Master and Disciple original from the Martial Arts, and anchors their focus on sensitive education that emerges from this relationship. The interest here is knowing how the tradition of millenarian teachings is passed through the years, and how it gives from the relationship of Master and Disciple. To that end, I lean me in that context and also reflect on my experience as a Disciple of the Martial Arts, to that end, I lean me in that context and also reflect on my experience as a Disciple of the Martial Arts, and is from the immemorial fund that can give voice to that experience, through my body attached in the world of significations in which the experience lived is narrated by the story. Anchored from the phenomenological attitude from the philosopher french Maurice Merleau-Ponty, I think this research on three central pillars to guide our study categories, namely: the lived experience, body and liberty. Still, as a form of highlighting this sensitive work, beyond the texts of the philosopher Merleau-Ponty, we bring our dialogue of the cinema, literature and the writings of some the Masters of Martial Arts. For that, I think this research as a journey, where it, Master and Disciple march together in the ways of Martial Arts, baptizing and celebrating this sensitive education from that relationship affective and empathic